2011
DOI: 10.1002/iub.427
|View full text |Cite
|
Sign up to set email alerts
|

miR‐210: More than a silent player in hypoxia

Abstract: Summary Multiple studies have consistently established that miR (microRNA)-210 induction is a feature of the hypoxic response in both normal and transformed cells. Here, we discuss the emerging biochemical functions of this miRNA and anticipate potential clinical applications. miR-210 is a robust target of hypoxia-inducible factor, and its overexpression has been detected in a variety of cardiovascular diseases and solid tumors. High levels of miR-210 have been linked to an in vivo hypoxic signature and associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
242
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(254 citation statements)
references
References 61 publications
(92 reference statements)
12
242
0
Order By: Relevance
“…5). This raises the question how miR-210, which has previously been associated with hypoxia response 24 , may affect memory. Considering the extreme sensitivity of neural structures and neurons to hypoxia 57 , we suggest small changes to oxygen levels in metabolic activity neurons may induce expression of miR-210, which in turn targets key molecules including asparagine synthetase and actin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5). This raises the question how miR-210, which has previously been associated with hypoxia response 24 , may affect memory. Considering the extreme sensitivity of neural structures and neurons to hypoxia 57 , we suggest small changes to oxygen levels in metabolic activity neurons may induce expression of miR-210, which in turn targets key molecules including asparagine synthetase and actin.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, miR-210 is an independent RNA gene that functions in hypoxia response including targeting the Ephrin-A3 receptor in the nervous system 24,25 . miR-210 is also noted to be differentially expressed in bees performing different behavioural tasks such as brood care and foraging 26 .…”
Section: Articlementioning
confidence: 99%
“…For example, component of the apoptotic machinery were found to be potentially targeted by HRMs: BID (miR-23), BIM (miR-24); CASP3 (miR-30), CASP 7 (miR-23), APAF1 (miR-27), BAK1 (miR-26), Bnip3L (miR-23) [91]. Recently experimentally data confirmed an important regulatory role in HIF-1 for miR-210, 26 and 181 hypoxia-induced microRNAs [91,92] In addition to the microRNAs that respond to hypoxia by up-regulation of their expression, the following microRNAs were identified as downregulated in hypoxic cells: miR-122a, miR-565, miR-195, miR-30e-5p, miR-374, 19a, miR-101, miR-424, miR-29b, miR-186, miR-141, miR-320, miR-422b, and miR-197 in SCC cells; miR-15b, miR-16, miR-20a, miR-20b, 30b and miR-224 in CNE cells, and miR-424 in trophoblasts [93]. In addition it has been reported that several microRNAs, including miR-16, miR-20a, miR-20b and miR-320, control expression of VEGF [92,93].…”
Section: Micrornas and Hypoxiamentioning
confidence: 99%
“…miRNA perturbations are relatively prevalent and highly involved in the development of a number of human diseases, including cancer, viral infections, and muscular and cardiovascular diseases (14). As an important subtype of miRNAs, miR-210 expression appears to be associated with a variety of physiological processes, such as mitochondrial metabolism, cell survival, DNA damage repair, proliferation, angiogenesis, transport and protein modification (15,16). Notably, it has previously been reported that miR-210 may be involved in the occurrence, development and prognosis of numerous diseases and types of cancer.…”
Section: Introductionmentioning
confidence: 99%